Synthesis and Crystal Structure of the Bioinorganic Complex [Sb(Hedta)]·2H2O - Di Li; Guo-Qing Zhong (Bioinorganic Chemistry and Applications)
The antimony(III) complex [Sb(Hedta)]·2H2O was synthesized with ethylenediaminetetraacetic acid (H4edta) and antimonous oxide as main raw materials in aqueous solution. The composition and structure of the complex were characterized by elemental analysis, infrared spectra, single crystal X-ray diffraction, X-ray powder diffraction, thermogravimetry, and differential scanning calorimetry. The crystal structure of the antimony(III) complex belongs to orthorhombic system, space group Pna2(1), with cell parameters of a=18.4823(18) Å, b=10.9408(12) Å, c=7.3671(5) Å, V=1489.7(2) Å3, Z=4, and Dc=1.993 g cm−3. The Sb(III) ion is five-coordinated by two amido N atoms and three carboxyl O atoms from a single Hedta3− ligand, forming a distorted trigonal bipyramid geometry. The thermal decomposition processes of the complex include dehydration, oxidation, and pyrolysis of the ligand, and the last residue is Sb2O3 at the temperature of 570°C.